The Incidence of Hypertension Among the Elderly in Boyolali Regency - Annisa Pramitasari; Widya Hari Cahyati; Yuni Wijayanti (Universitas Negeri Semarang, 2026)
Hypertension is one of the most common non-communicable diseases (NCDs) and remains a major public health concern worldwide. Although the prevalence of hypertension in Indonesia declined from 34.1% in 2018 to 30.8% in 2023, this figure still falls short of the national Sustainable Development Goals (SDGs) target of 25%. The prevalence of hypertension increases with age, recorded at 13.2% among individuals aged 18–24 years, 45.3% among those aged 45–54 years, and as high as 63.8% among individuals aged 75 years and older. This study aimed to identify the factors associated with the incidence of hypertension among the elderly in Boyolali Regency. The research employed an analytical observational design with a case control approach. Data were collected from December 2024 to February 2025, involving 164 respondents consisting of 82 elderly individuals in the case group and 82 in the control group. The variables examined included sex, family history, marital status, physical activity, obesity, smoking habits, and coffee consumption. Univariate analysis was used to describe the basic characteristics of the respondents, while bivariate analysis using the Chi-Square test was conducted to examine the relationship between the independent variables and the incidence of hypertension. The study findings revealed significant associations between family history, marital status, physical activity, obesity, and coffee consumption with the incidence of hypertension among the elderly in Boyolali Regency.